Experimental infection of castrated lambs with Mycoplasma agalactiae. - MacOwan, K. J. (Cambridge University Press, 1984)
The course of experimental infection in groups of 6-month-old castrated lambs with field isolates of Mycoplasma agalactiae from France was followed culturally and serologically for 7 months. Infection with an ovine field isolate following inoculation by different routes and contact exposure was compared with that caused similarly by a caprine field isolate. The prolonged infections produced were symptomless apart from limited arthritis in one animal inoculated with the isolate from sheep and increased lachrymation in another associated with the goat isolate. The ovine isolate was more virulent in that ante- and post-mortem recoveries of the organism were more consistent and the serological responses more pronounced. Serological responses varied between animals and between strain infections, and the results of the film inhibition test were more consistent than those of the complement fixation test. The limitations of both these tests for detecting carrier infections are discussed.